THE EFFECT OF PUBLIC SERVICE QUALITY ON PUBLIC SATISFACTION AT THE WEST PURWOKERTO DISTRICT OFFICE - Sartono Sartono; Salva Asyraf Hanidar; Devit Bagus Indranika (DYNAMICS: Journal Of Public Administration, 2026)
Public satisfaction can be created if people’s expectations match what they get, or even exceed their expectations. Public service quality has several aspects that can affect people satisfaction, which consists of five aspects such as Tangibles, Raliability, Responsiveness, Assurance, and Empathy. That research was conducted at the West Purwokerto Distict Office. The purpose of this study was to determine and analyze the effect of service quality consisting of aspects of Tangibles, Reliability, Resposiveness, Assurance, and Empathy on people satisfaction at the West Purwokerto District Office. This research uses survey method. The techniques used to analyze the data in this study are Kendall Tau Correlation, Kendall W Concordance, and Ordinal Regression. The result of the analysis showed that: (1) There is a positive and significant influence between Tangibles on people satisfaction of 0,377 or 37,7%. (2) There is a positive and significant influence between Reliability on people satisfaction of 0,485 or 48,5%. (3) There is a positive and significant influence between Responsiveness on people satisfaction of 0,489 or 48,9%. (4) There is a positive and significant influence between Assurance on people satisfaction of 0,452 or 45,2%. (5) There is a positive and significant influence between Empathy on people satisfaction of 0,493 or 49,3%. (6) There is a positive and significant influence between Tangibles, Reliability, Responsiveness, Assurance, and Empathy on people satisfaction of 0,586 or 58,6%. This proves that all independent variables can influence the dependent variable both partially and simultaneously.